2020
DOI: 10.1007/s41603-020-00124-0
|View full text |Cite
|
Sign up to set email alerts
|

Complicity and Synergy Between Bolsonaro and Brazilian Evangelicals in COVID-19 Times: Adherence to Scientific Negationism for Political-Religious Reasons

Abstract: Since the beginning of the COVID-19 pandemic, the article discusses how a large part of the Brazilian evangelical churches resorted to informational disorder and disinformation as instruments to deny the severity of the disease. It also discusses how the production, endorsement, and support of false news served to establish a support platform for the President of the Republic of Brazil, Jair Messias Bolsonaro, with emphasis on the month of March, when the pandemic hit Brazil, until mid-April 2020, when religio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
10
0
2
Order By: Relevance
“…Analysing his statement during the public debate, Ndinojuo et al, 2020, observed that it fell within the sphere of CTs, not necessarily because he was wrong, but because he failed to provide any empirical foundation to his claim [ 90 ]. The reluctance that the Brazilian government has had to impose the lockdown is well known; in Brazil, far-right political parties are closely linked to Evangelical churches, within a mutually dependent relationship, and Bolsonarism also used the religion as a political force during the pandemic [ 91 ]. The approach of Bolsonaro and his allied evangelical representation is an example of the minimization of the dangers of the pandemic that, even if it does not technically comply with the definition of a CT, shares its underlying paradigms and consequences in terms of health risk for the population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysing his statement during the public debate, Ndinojuo et al, 2020, observed that it fell within the sphere of CTs, not necessarily because he was wrong, but because he failed to provide any empirical foundation to his claim [ 90 ]. The reluctance that the Brazilian government has had to impose the lockdown is well known; in Brazil, far-right political parties are closely linked to Evangelical churches, within a mutually dependent relationship, and Bolsonarism also used the religion as a political force during the pandemic [ 91 ]. The approach of Bolsonaro and his allied evangelical representation is an example of the minimization of the dangers of the pandemic that, even if it does not technically comply with the definition of a CT, shares its underlying paradigms and consequences in terms of health risk for the population.…”
Section: Resultsmentioning
confidence: 99%
“…The press was accused of spreading panic, and a refined minimization attitude was applied with an argumentative strategy that resorted to rhetoric, allusion and unspecific religious themes such as “panic is devastating to the immune system, a poison”, “the church is an emotional hospital”, and “the blood of Christ is the greatest immunizing power that exists, we are covered by the blood of Jesus” [ 91 ]. This most likely created an overlap between the political and religious faith of the audience and their critical and rational capacity to interpret the events.…”
Section: Resultsmentioning
confidence: 99%
“…The ideological issue promotes the conformity of ideas or behaviors through the feeling of belonging to a group [ 23 ]. This same ideological issue can influence the rejection of technical and scientific information (negationism) [ 44 ], that is, we can observe the egocentric bias and the decrease in the exchange of cultural traits in the system. Therefore, the models that transmit these bubbles would not suffer sanctions, since the “social bubble” would accept the diffusion of both adapted and maladaptive traits of a model belonging to the group.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar da Organização Mundial da Saúde (OMS) aconselhar o uso de máscaras em locais públicos (BBC, 2020), o governo dos EUA não decretou uma obrigação federal sobre o uso de máscara. No Brasil, houve duas trocas de Ministro da Saúde durante a pandemia e as recomendações relacionadas aos cuidados sanitários provenientes do governo foram discordantes com as da OMS, resultando em um embate entre o presidente e governadores dos estados, que adotaram medidas mais rígidas de isolamento social (Kibuuka, 2020). Na Índia, destaca-se que o governo negou a força da "transmissão comunitária" da COVID-19, divulgando dados considerados confusos por especialistas e médicos, enfermeiros e jornalistas acusam o governo de terem sido reprimidos (Scientific American, 2020).…”
Section: Crises Decorrentesunclassified